Análisis y aplicación de la programación orientada a agentes e interacción de multiagentes con plataforma jade - Obando Toasa, Evelyn Estefania (2016)
This technical project is carried out in order to determine the differences between Object Oriented Programming (POO) and Agents Oriented Programming (POA) as these two technologies are very useful for software development, we will focus more on the use of agents and the POA. So maked an analysis to obtain information, detailed examination of parts, know their characteristics and draw conclusions will study the use and management of the JADE platform for the development of agents implemented in Java and will study a methodology for development of agents which may be to structure, plan and control the development agents process. Develop a demo application (desktop) auction of books with POA and POO. Analyze the efficiency of POO and POA using a data set and finally with the data preliminarily obtained show graphs enabling the difference between OOP and POA. On the other hand we will study the interaction between agents which make up the multi-agent systems this is done through the FIPA-ACL protocol that is responsible for establishing communication through messages agents such as (Inform, Request, Query- ref etc.) for communicating are also used behaviors too. With the results we can determine that it is feasible the use of agents in the development of software as it is helpful for his capacity of autonomy, proactivity and communication with other agents.